Laparoscopic ovariectomy in dogs and cats - Ferreira, Giseli dos Santos (2012)
ABSTRACT. Ferreira G.S., Franco C.A.D., Santos C.L., Atallah F.A., Estupnañ O.F.T., Silva S.J.Q. & Oliveira A.L.A. [Laparoscopic ovariectomy in dogs and cats]. Ovariectomia laparoscópica em cadelas e gatas. Revista Brasileira de Medicina Veterinária, 35(Supl. 1):55-60, 2013. Curso de Pós-Graduação em Ciência Animal, Universidade Estadual do Norte Fluminense Darcy Ribeiro, Av. Alberto Lamego, 2000, Parque Califórnia, Campos dos Goytacazes, RJ 28013-602, Brasil. E-mail: gigisanfer@gmail.com Ovariosalpingohisterectomy (OSH) and ovariectomy (OVE) consist of effective contraceptive methods used in dogs and cats. The minimally invasive surgical techniques (TCMI) are used by veterinary professionals with the goal of Minimar the postoperative complications. The aim of this study was the evaluation of complications during the peri-and post-operative dogs and cats undergoing ovariectomy (OVE) by laparoscopy using monopolar electrosurgery system, as well as compare the surgical time obtained after the procedure in both species. Were operated 6 bitches and 6 cats, No Restriction Race (SRR), through the technique for laparoscopic ovariectomy. After inspection of the cavity with the laparoscope was performed to identify and hold the right ovary, the same being pulled allowing hemostasis using monopolar electrocautery for coagulation complex ovarian arterial (CAVO) and ligaments own suspensory ligament of the ovary, then sectioned with scissors. The same procedure was performed in the left ovary. There were no intraoperative complications that culminate with the conversion from laparoscopy to laparotomy, in any of the operated animals. The mean operative time of six dogs was operated 50min07s ± 16min2s and cats of 25min33s ± 7min01s. Among the postoperative complications occurred, a dog developed subcutaneous emphysema and other moderate bitch presented seroma in two portals. We conclude that the technique of laparoscopic ovariectomy using monopolar electrosurgery, provides satisfactory results with low morbidity. The mean operative time of operated cats was lower than the bitches. The postoperative complications were minimal, occurring only in bitches.